Entre la textualité et l’intertextualité ou de la structure d’un projet d’architecture - Walkiewicz, Barbara (Studia Romanica Posnaniensia, 2012)
This paper is an attempt to describe a building design as a hypertext genre. It represents a single– or multi-volume document that has to be submitted when applying for a planning permission issued by an appropriate administrative authority, usu. by Building Surveyors. Its broad thematic scope provides the best proof of its multidisciplinary character – indeed, it bears witness to the complexity of investment process which has to result eventually in the completion of a new building. Building designs consist of texts featuring various genres that belong to different discourse types – apart from administrative ones, they involve texts dealing with architecture, urban architecture, structural engineering, interior fit-outs, electrical and heating facilities, sanitary fittings. Law regulations precise the exact content of a building design, which heavily depends on the putative function of a building, its degree of complexity and environmental setting. A building design thus turns out to be a multilayered genre whose composition is related to extra linguistic factors (design location and its function). It exhibits features typical of hypertext genres: non-sequentiality (non-linearity), component independence of hyperstructure, polyphony (many authors), primacy of global coherence and interactivity. All the characteristics make it difficult to apply traditional models of describing linear texts to building designs, thus proving that the dividing line between text and hypertext genres is independent of the media boundary.